Atypical Spoilage Microorganisms inArgentinean Yogurts: Gas-ProducingMoldsandBacteria of the Genus Gluconobacter - Capra, María Luján (2024)
Microbiological spoilage of food leads to products unfit for consumption, and their discardingleadstosignificant economic losses for the food industry. During storage, fresh foods offer available niches for the survival andgrowth of undesirable microorganisms. In dairy products, data regarding spoilage and/or pathogenic bacteria is betterdocumented than those for molds and yeasts. Dairy products, due to their refrigerated storage and production fromheattreated milk, are less susceptible to mold contamination compared to fruits and vegetables. The dominant microbiotainfermented dairy products also contributes to acidifying the medium, further reducing the risk of spoilage. However, evencheeses and yogurts may be susceptible to mold contamination. Atypical cases of yogurt samples containingspoilagemicroorganisms not previously reported (molds producing gas and bacteria of the genus Gluconobacter) in Argentineanfermented milks are presented here. For yogurt, in particular, the "classic" altering organisms were always beingyeasts, and in other countries, molds belonging to the genus Aspergillus.